Anti-foaming admixture (AFA) and its influences on the properties of a fresh self-compacting concrete mix - Łaźniewska-Piekarczyk, Beata; Szwabowski, Janusz (Journal of Civil Engineering and Management, 2012)
The properties of a concrete mix should secure the self-elimination of needless air bubbles from its volume. What is interesting, these properties are not taken into consideration in commonly used self-compacting tests. On the basis of different tests concerning self-compacting concrete mixes, it has been discovered that too high air content in their volume was a result of a superplasticiser, in spite of meeting the self-compactibility criteria. To decrease too high air volume in SCC, the use of an anti-foaming admixture (AFA) is proposed by the authors. Because of an AFA introduced into a self-compacting mix, air-content in this mix is decreased, mix flow diameter is increased and flow time is decreased. In case of a mix incorporating an AFA, its high flowability does not cause segregation of the mix, which is possible in case of SCC incorporating only a superplasticiser. However, time of introduction of an AFA is essential to get higher flowability degree, but is not important in achieving low air volume in SCC. Moreover, the workability of a self-compacting mix with an AFA keeps the same level for a longer period of time. Priešpučio (AFA) įtaka susitankinančio betono mišinio savybėms Santrauka. Betono mišinio sudėtis turi būti tokių savybių, kad užtikrintų nereikalingo oro kiekio pasišalinimą. Įdomu, kad į šias savybes dažniausiai nėra atsižvelgiama atliekant susitankinančio betono bandymus. Remiantis įvairiais susitankinančio betono mišinio tyrimais, buvo nustatyta, kad per dideliam oro kiekiui įtakos turi superplastikliai, nepaisant to, kad jie turi tankinančių savybių. Norint susitankinančio betono mišinyje (SCC) sumažinti per didelį oro kiekį, siūloma naudoti priešputį (AFA). Kadangi AFA įterpimas į susitankinančio betono mišinį sumažina oro kiekį, padidėja mišinio pasklidimo skersmuo ir sumažėja pasklidimo trukmė. Jeigu mišinio sudėtyje yra AFA, mišinio takumas neskatina išsisluoksniavimo, o tai gali atsitikti naudojant SCC tik superplastiklį. Tačiau AFA įterpimo trukmė turi poveikį mišinio takumo laipsniui, bet nėra reikšminga pasiektam mažam oro kiekiui SCC. Be to, susitankinančio betono mišinio su AFA klojumas ilgesnį laiką išlieka to paties lygmens. Reikšminiai žodžiai: priešputis (AFA), oro tūrio sumažėjimas, susitankinantis betonas (SCC), superplastiklis, reologinės savybės, klojumo nuostoliai.